Atypical bacterial co‐infections among patients with COVID‐19: A study from India. Issue 1 (15th September 2021) - Chaudhry, Rama; Sreenath, K; Batra, Priyam; Vinayaraj, EV; Rathor, Nisha; Saikiran, KVP; Aravindan, Ajisha; Singh, Vishwajeet; Brijwal, Megha; Soneja, Manish; Verma, Nishant; Subramanium, Rajeshwari; et al.
Abstract: Emerging evidence shows co‐infection with atypical bacteria in coronavirus disease 2019 (COVID‐19) patients. Respiratory illness caused by atypical bacteria such as Mycoplasma pneumoniae, Chlamydia pneumoniae, and Legionella pneumophila may show overlapping manifestations and imaging features with COVID‐19 causing clinical and laboratory diagnostic issues. We conducted a prospective study to identify co‐infections with SARS‐CoV‐2 and atypical bacteria in an Indian tertiary hospital. From June 2020 to January 2021, a total of 194 patients with laboratory‐confirmed COVID‐19 were also tested for atypical bacterial pathogens. For diagnosing M. pneumoniae, a real‐time polymerase chain reaction (PCR) assay and serology (IgM ELISA) were performed. C. pneumoniae diagnosis was made based on IgM serology. L. pneumophila diagnosis was based on PCR or urinary antigen testing. Clinical and epidemiological features of SARS‐CoV‐2 and atypical bacteria‐positive and ‐negative patient groups were compared. Of the 194 patients admitted with COVID‐19, 17 (8.8%) were also diagnosed with M. pneumoniae ( n  = 10) or C. pneumoniae infection ( n  = 7). Confusion, headache, and bilateral infiltrate were found more frequently in the SARS CoV‐2 and atypical bacteria co‐infection group. Patients in the M. pneumoniae or C. pneumoniae co‐infection group were more likely to develop ARDS, required ventilatory support, had a longer hospital length of stay, and higher fatality rate compared to patients with only SARS‐CoV‐2. Our report highlights co‐infection with bacteria causing atypical pneumonia should be considered in patients with SARS‐CoV‐2 depending on the clinical context. Timely identification of co‐existing pathogens can provide pathogen‐targeted treatment and prevent fatal outcomes of patients infected with SARS‐CoV‐2 during the current pandemic.